The role of radiation therapy in cutaneous melanoma - Morysiński, Tadeusz (Contemporary Oncology/Współczesna Onkologia, 2003)
The indications for adjuvant radiotherapy in cutaneous melanoma patients after therapeutic radical lymph node dissection are as follows presence of nodal extracapsular invasion, infiltration of subcutaneous tissue, infiltration of lymphatic vessels by melanoma cells and bulky involvement of lymph nodes. The indications for radiotherapy of primary tumors include impossibility of radical surgery treatment and recurrence in the scar after primary lesion excision. There were no significant differences in the survival time for patients treated or not with adjuvant radiotherapy after axillary or inguinal lymphadenectomy although the patients who have undergone adjuvant radiotherapy as a selective group demonstrated worse prognostic factors. It is possible to reach complete cure using high fraction doses at 600–800 cGy. This type of treatment was well-tolerated; any significant complications were not observed after radiotherapy with high fractioned doses. The results of radiotherapy in bone and brain metastases are poor.